ECONOMIC INFLUENCES ON CURRENCY FLUCTUATIONS: INSIGHTS FROM SUDAN - Taha, Laila Ali; Moustafa, Kareem Saleh (Ayden International Journal of Banking, Finance and Technology, 2024)
Macroeconomic Factor, exchange rate, evidence and Sudan This study examines the determinants of exchange rate and their impact on exchange rate volatility in Sudan using the ARDL model, Vector Error Correction mechanism and several tests such as Wald test, heteroskedasticity consistence covariance (White) test, HAC consistent covariance (Newey-West) test, and inferential statistics. The research documents that balance of trade, gold purchases, money supply, inflation and foreign reserves are the main factors affecting the exchange rate in Sudan. The study finds that the exchange rate system in Sudan has no impact on the stability of the exchange rate, as the exchange rate continuously deteriorated and fluctuated throughout the period under study. The paper adds to the existing literature by providing empirical evidence on the determinants of exchange rate in a small economy such as Sudan, where an independent monetary policy is difficult to execute. The findings of this study may have implications for policymakers, particularly those in small economies, in choosing the appropriate exchange rate system.